2019
DOI: 10.14710/jmr.v8i4.25193
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Citra Sentinel-2 untuk Pemetaan Sebaran Material Padatan Tersuspensi Di Muara Sungai Wulan Demak

Abstract: ABSTRAK : Sungai Wulan yang terletak di Kabupaten Demak digunakan masyarakat sebagai jalur keluar dan masuknya kapal nelayan serta saluran pembuangan utama. Hal tersebut berdampak pada besarnya kandungan material padatan tersuspensi yang terdapat pada sungai. Pengamatan sebaran material padatan tersuspensi dibutuhkan untuk mengetahui pola sedimentasi dan penilaian kualitas air. Tujuan dari penelitian ini adalah untuk mengetahui sebaran material padatan tersuspensi di muara Sungai Wulan menggunakan metode pengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
2
0
7
Order By: Relevance
“…However, the values are comparable. For example, the R 2 values of each model are 0.5140 and 0.5056 by using validation data in this study, while they are 0.4707 and 0.4735 by using validation data in other locations [28], [31] for TSS models 1 and 4, respectively (see 'This Study' and 'Other Validation Data' column for TSS model 1 and 4 in Nurgiantoro & Jaelani [30] Other Validation Data [28], [31] This Study Nurgiantoro et al [29] Nurgiantoro & Jaelani [30] Other Validation Data [28] Nurgiantoro & Jaelani [30] Other Validation Data [28], [31] This Study Nurgiantoro et al [29] Nurgiantoro & Jaelani [30] Other Validation Data [28] [13], [15], [16], [23], [26]- [28], [53], [54]. Moreover, it also provides favourable results in estimating TSS concentration.…”
Section: Evaluation and Comparison Between All Modelsmentioning
confidence: 99%
“…However, the values are comparable. For example, the R 2 values of each model are 0.5140 and 0.5056 by using validation data in this study, while they are 0.4707 and 0.4735 by using validation data in other locations [28], [31] for TSS models 1 and 4, respectively (see 'This Study' and 'Other Validation Data' column for TSS model 1 and 4 in Nurgiantoro & Jaelani [30] Other Validation Data [28], [31] This Study Nurgiantoro et al [29] Nurgiantoro & Jaelani [30] Other Validation Data [28] Nurgiantoro & Jaelani [30] Other Validation Data [28], [31] This Study Nurgiantoro et al [29] Nurgiantoro & Jaelani [30] Other Validation Data [28] [13], [15], [16], [23], [26]- [28], [53], [54]. Moreover, it also provides favourable results in estimating TSS concentration.…”
Section: Evaluation and Comparison Between All Modelsmentioning
confidence: 99%
“…Distribusi dari kondisi TSS waduk dapat menunjukkan gambaran mengenai proses sedimentasi di waduk tersebut. Perairan waduk yang memiliki kadar TSS tinggi juga cenderung akan mengalami sedimentasi yang tinggi (Prasetiyo, Rochaddi, & Satriadi, 2019). Distribusi TSS sangat bergantung pada pola pemanfaatan waduk.…”
Section: Pendahuluanunclassified
“…Waduk Gondang memberikan manfaat yang besar bagi perkembangan daerah-daerah disekitarnya. Waduk ini dimanfaatkan sebagai pengairan atau irigasi pertanian, budidaya perikanan serta objek wisata (Prasetiyo et al, 2019). Namun, seiring berjalannya waktu Waduk Gondang mengalami beberapa permasalahan, seperti penyempitan area luasan waduk, pendangkalan waduk serta penurunan kualitas air waduk.…”
Section: Pendahuluanunclassified
“…In Zainab et al [9], the relationship between RGB color and chlorophyll-a content was found; it is the best equation in the form of an exponential equation with a correlation coefficient of 0.767. In addition, in other studies [10], [11] studied the relationship between RGB colors for the distribution of solid materials, and the best equation was obtained, i.e., the exponential equation with a correlation coefficient of 0.9336 and 0.9075, respectively.…”
Section: Introductionmentioning
confidence: 99%